WOMEN AND WORSHIP: THE SIKH PERSPECTIVE - Bala, Shashi (Journal of Dharma, 2020)
To study the status of women in any religion and her participation in religious worship and religious life, it is pertinent to go through its scriptural basis as well as its past history to evaluate its theological perspective and past and present practices about the contributions of women.